'Cosmopolitan from above': a Jewish experience in Hong Kong. Issue 5 (1st November 2016) - Zhou, Xun
Abstract: The case of Hong Kong provides a substantial re-examination of what it means to be a cosmopolitan from above, both historically in terms of real colonial presence and power – that of the British Empire at the height of its pink-flushed world domination – and as a 'model minority' under such circumstances as well as in the postcolonial world of modern Hong Kong. The history of the Jews in Hong Kong illustrates the pitfalls in assuming the view of 'cosmopolitan of the above' is uniform or indeed 'from above'. The confusion of the cosmopolitan with the utopian goals of transhistorical views of mobility with the lived practice of Jews in British and now Chinese Hong Kong is a powerful corrective of this view. Focusing on Hong Kong, this former British Colony and now a Special Administrative Region (SAR) of the People's Republic of China, situated simultaneously at the centre and at the periphery of debates about the cosmopolitan, this article adds a new dimension to the parallel discussions of Jewish cosmopolitanism in Europe and North America.